Методи «когнітивного радіо» у системах мобільного зв’язку 5G - Савченко, Р. О.; Селіванов, К. О.; Москалець, М. В. (ХНУРЕ, 2022)
The subject of the study are ways to apply the principles of SDR technology in the segment of high-speed data transmission system in the mobile communication system of the GSM standard, as well as possible options for building equipment of the data transmission subsystem on the principles of spectrum adaptation with other mobile communication systems. combined frequency bands.The analysis of possible ways to increase the data transfer rate in GSM mobile communication networks with the use of cognitive radio and SDR technologies focused on high - speed data transmission is carried out.
Keywords: 5G; мобільний зв'язок; когнітивне радіо